Anton Piller Order: its growth and development / Abd Karim Rahman Hamzah - Rahman Hamzah, Abd Karim (Faculty of Law, 1983)
An injunction is an order by the Court to a party with effect that he shall do or refrain from doing a particular act. In England, the jurisdiction is governed by the Court of Judicature Act 1925. In Malaysia the Specific Relief Act 1950 (Revised 1974) granted to the High Court, the discretion to grant temporary or perpetual injunction. The Anton Piller Order is a new development in the law of injunction. It came into being after the case Anton Piller KG. Vs Manufacturing Process Ltd (1976) I All E.R. 779 which laid down the foundation for the Anton Piller Order.